Registration of mortgage contracts - documents that represent the legal basis for making changes to the mortgaged real estate - Bodrozic, Milana (Glasnik Advokatske komore Vojvodine, 2024)
The paper focuses on the formal and practical problems of the competent Real Estate Cadastre Service when implementing changes to mortgaged real estate. By registering the mortgage contract in the database of the real estate cadastre, the mortgage produces a legal effect. Making changes to the mortgaged real estate changes the subject of the mortgage. The owner of the real estate cannot change the subject of the mortgage without the consent of the mortgage creditor. As every factual change is conditioned by registration or registration in the real estate cadastre, it is necessary to submit documents that represent the legal basis for registration. Whether the owner of the mortgaged real estate acted in accordance with the legal provisions, when changing the subject of the mortgage, we will perform an analysis in specific cases, in such a way that we will start from the assumption of whose will the change in the real estate occurs.